2014
DOI: 10.1038/jhg.2014.55
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthetic and functional defects in newly identified SLC4A11 mutants and absence of COL8A2 mutations in Fuchs endothelial corneal dystrophy

Abstract: Late-onset Fuchs endothelial corneal dystrophy (FECD) shows genetic heterogeneity. Identification of SLC4A11 as a candidate gene for congenital hereditary endothelial dystrophy with similar corneal endothelial defects as FECD and reduced mRNA expression of SLC4A11 in the endothelium of FECD cases suggested that this gene may also be involved in pathogenesis of FECD. Mutations in SLC4A11 give rise to SLC4A11 protein marked by retention in the endoplasmic reticulum as a result of mis-folding. We screened 45 spor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 39 publications
1
25
0
2
Order By: Relevance
“…Furthermore, a prior serial analysis of gene expression (SAGE) study found SLC4A11 to be underexpressed in the CE of Fuchs patients [35]. SLC4A11 was also of particular interest because SLC4A11 mutations have been reported to be associated with some cases of late-onset FECD [40, 41]. GUCY2C was selected for validation because it had the most significantly methylated promoter CpG site in the FECD samples (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, a prior serial analysis of gene expression (SAGE) study found SLC4A11 to be underexpressed in the CE of Fuchs patients [35]. SLC4A11 was also of particular interest because SLC4A11 mutations have been reported to be associated with some cases of late-onset FECD [40, 41]. GUCY2C was selected for validation because it had the most significantly methylated promoter CpG site in the FECD samples (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…A group of mutations in SLC4A11, encoding a sodium-borate cotransporter NaBC1, were also identified (Riazuddin et al, 2010a;Soumittra et al, 2014;Vithana et al, 2008). This transporter is located in the basolateral membrane of endothelial cells and was shown to facilitate transmembrane water movement (Vilas et al, 2013); FECD SLC4A11 mutations expressed in cells show intracellular retention of the protein (Vilas et al, 2012).…”
Section: Genetic Basismentioning
confidence: 96%
“…Mixed evidence suggests that heterozygous variants in SLC4A11 may be associated with FECD4 (OMIM#613268). [89][90][91] Inconclusive segregation analysis has been reported in these families (reviewed by Aldave et al). 75 As described elsewhere in this review, homozygous variants in SLC4A11 result in CHED, yet parents of patients with CHED do not seem to present with late-onset FECD.…”
Section: Fuchs Endothelial Corneal Dystrophymentioning
confidence: 94%